Angular‐dependent spectral responsivity—Traceable measurements on optical losses in PV devices. (27th November 2017) - Plag, F.; Kröger, I.; Fey, T.; Witt, F.; Winter, S.
Abstract: Angular‐dependent optical losses can have an effect on the spectral responsivity of photovoltaic devices. When these devices with differing angular‐dependent spectral responsivity are exposed to incident direct and diffuse solar spectral irradiance they will perform differently compared with direct and perpendicular beam exposure only. However, if the angular and polarization‐dependent spectral responsivity is known, optical losses can be determined for any given angular distributed solar spectrum. Here, we show the capabilities of a newly developed laser‐based calibration facility for traceable measurements on reference solar cells angular‐dependent spectral responsivity for device areas of up to 156 × 156 mm 2 . Our investigation is focused on a comprehensive analysis on all related measurement uncertainties. We present the results of measurements on a variety of reference solar cells as well as an industry type solar cell with and without encapsulation showing that strong differences in their optical properties occur. Additionally, we compare the results obtained with a conventional broadband characterization approach using a halogen lamp as light source. An agreement, better than 1%, was observed for the broadband measurement and the spectral measurements weighted by the spectral responsivity and the lamp spectrum. It is shown why different light sources lead to different angular‐dependent responsivities. In conclusion, validation measurements of solar simulator‐based or natural sunlight‐based angular responsivity facilities at testing and calibrations laboratories can be offered. Furthermore, by means of traceable angular‐dependent spectral responsivity measurements and multidimensional models under consideration of diffuse light components, optical losses for photovoltaic performance measurements, energy rating, and related uncertainties can be studied. Abstract : "eye‐catching"‐Figure: Effect of encapsulation on a typical c‐Si solar cell: Deviation from ideal cosine response of an industrial large area c‐Si solar cell and a mini‐module made from the same type of solar cell. The angular‐dependent responsivity significantly improves due to the encapsulation, leading even to a relative overperformance in the infrared region.